Pain in Hemophilia: Unexplored Role of Oxidative Stress - Raghda Fouda; Donovan A. Argueta; Kalpna Gupta (MDPI AG, 2022)
Hemophilia is the most common X-linked bleeding diathesis caused by the genetic deficiency of coagulation factors VIII or IX. Despite treatment advances and improvements in clinical management to prevent bleeding, management of acute and chronic pain remains to be established. Repeated bleeding of the joints leads to arthropathy, causing pain in hemophilia. However, mechanisms underlying the pathogenesis of pain in hemophilia remain underexamined. Herein, we describe the novel perspectives on the role for oxidative stress in the periphery and the central nervous system that may contribute to pain in hemophilia. Specifically, we cross examine preclinical and clinical studies that address the contribution of oxidative stress in hemophilia and related diseases that affect synovial tissue to induce acute and potentially chronic pain. This understanding would help provide potential treatable targets using antioxidants to ameliorate pain in hemophilia.